2015
DOI: 10.1039/c5ra10408d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reduction of CO2 using molybdenum-doped titanate nanotubes in a MEA solution

Abstract: In this study, the photocatalytic reduction of CO2 in monoethanolamine solution to form valuable energy sources was investigated using Mo-doped TNTs photocatalysts for the first time. The results revealed that the structure of Mo-doped TNTs was changed with the increase of calcination temperature. For Mo-doped TNTs calcined at 500 °C, the partial corruption of titanate nanotubes into anatase particles caused the reduction of Mo species from Mo 6+ to Mo 5+ and produced oxygen vacancies, which resulted in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Introduction of some metal cations (such as Cu, Co, , Ni, Ce, , Mo, In, Ti, V, and Cr) into the host framework not only modifies the crystallinity of TiO 2 but also influences its light absorption properties. Also, the enhanced red-shifting from the UV region to longer wavelengths in the visible region can be observed with enhancing cation-doping levels. For example, Cu-doped TiO 2 shows a slightly but steadily decreased bandgap upon enhancing Cu­(II) concentration from 0 to 3 mol % and has the potential to enhance the formation of HCOOH and CO in the presence of sulfide as an electron donor . Ola and Maroto-Valer have reported that the absorption spectra of Cu-based TiO 2 showed an increased shift in the visible light with enhancing Cu loading concentration in comparison with pure TiO 2 .…”
Section: Photocatalysts For One-step Excitation Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Introduction of some metal cations (such as Cu, Co, , Ni, Ce, , Mo, In, Ti, V, and Cr) into the host framework not only modifies the crystallinity of TiO 2 but also influences its light absorption properties. Also, the enhanced red-shifting from the UV region to longer wavelengths in the visible region can be observed with enhancing cation-doping levels. For example, Cu-doped TiO 2 shows a slightly but steadily decreased bandgap upon enhancing Cu­(II) concentration from 0 to 3 mol % and has the potential to enhance the formation of HCOOH and CO in the presence of sulfide as an electron donor . Ola and Maroto-Valer have reported that the absorption spectra of Cu-based TiO 2 showed an increased shift in the visible light with enhancing Cu loading concentration in comparison with pure TiO 2 .…”
Section: Photocatalysts For One-step Excitation Systemsmentioning
confidence: 99%
“…In the last 3 years, low-dimensional nanostructured TiO 2 were extensively applied in the photocatalytic CO 2 conversion. Among which, TiO 2 nanoparticles are still the most popular photocatalysts, ,, , , ,, ,, , while 1D ,,,,,, and 2D ,, nanomaterials are generally more attractive than their bulk and nanoparticle counterparts because they facilitate more efficient electron transport and exhibit higher surface-area-to-bulk-volume ratios. For instance, brookite TiO 2 nanorods with controllable aspect ratio were synthesized by using titanium ethoxide as Ti source .…”
Section: Photocatalysts For One-step Excitation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion of CO 2 could provide another alternative to the storage of CO 2 underground or in the deep ocean by producing value added chemicals while simultaneously addressing the energy shortage and global warming [2]. Among several existing technologies for CO 2 conversion to renewable fuels, photocatalytic reduction of CO 2 is a promising option that directly utilizes inexpensive and abundant solar energy [3][4][5]. Thus far, TiO 2 is commonly investigated for CO 2 photoreduction, however, its insufficient catalytic conversion efficiency still remains as the main bottleneck.…”
Section: Introductionmentioning
confidence: 99%